Just interests : victims, citizens and the potential for justice - Holder, Robyn (Elgar studies in law and society, 2018)
The idea of justice and the reality of justice are two very different things. Just Interests examines both concepts, offering accounts from lay people and legal officials to explore how the goals and interests of victims of crimes can be accommodated within the criminal justice process. Robyn Holder challenges the typical classification of 'victim' for those who have been victimized by violence, and re-positions them as members of a political community with diverse interests - both private and public. Departing from conventional approaches that see victims as a problem for law to contain, Holder draws on democratic principles of inclusion and deliberation to posit a criminal justice approach that mobilizes citizens to produce justice in their ordinary lives. This book will be of fundamental importance for analysts and advocates in governmental and non-governmental organizations to understand victims as citizens first and their engagements with criminal justice as citizenship practices. It will also be a valuable read for socio-legal scholars and researchers examining the constitutive nature of peoples and their public criminal law.